A finite volume model on unstructured meshes and application in computing two dimensional flows - Lịch, Trần Gia; Đức, Lê (Journal of Computer Science and Cybernetics, 2012)
Some methods in approximation of fluxes between adjacent cells have been proposed in context of the finite volume technique on unstructured meshes. A shallow water model has been developed for testing the proposed methods. The third order Adams-Bashforth scheme is used in integrating the governing equations. A filter has been designed to remove spurious waves. The model is tested on unstructured triangular meshes with some examples in literature.